2011
DOI: 10.15669/pnst.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Normalised Organ and Effective Doses to Adult Reference Computational Phantoms from Contemporary Computed Tomography Scanners

Abstract: The general-purpose Monte Carlo radiation transport code MCNPX has been used to simulate photon transport and energy deposition in anthropomorphic phantoms due to the x-ray exposure from the Philips iCT 256 and Siemens Definition CT scanners, together with the previously studied General Electric 9800. The MCNPX code was compiled with the Intel FORTRAN compiler and run on a Linux PC cluster. A patch has been successfully applied to reduce computing times by about 4%. The International Commission on Radiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Monte Carlo simulations Monte Carlo simulations have been performed [36][37][38] utilizing the general Monte Carlo N-Particle eXtended (MCNPX; Los Alamos National Laboratory, Los Alamos, NM) radiation transport code system v. 2.7.0, 39 installed on a dedicated personal computer cluster, comprising 10 calculation nodes and 1 server node. Simulations of dose have been completed in relation to a range of computational anthropomorphic phantoms, as discussed below, and to the measurement of CTDI (with a 100-mm pencil chamber) both at standard locations in the standard head and body CT dosimetry phantoms and also free-in-air on the axis of rotation.…”
Section: Methodsmentioning
confidence: 99%
“…Monte Carlo simulations Monte Carlo simulations have been performed [36][37][38] utilizing the general Monte Carlo N-Particle eXtended (MCNPX; Los Alamos National Laboratory, Los Alamos, NM) radiation transport code system v. 2.7.0, 39 installed on a dedicated personal computer cluster, comprising 10 calculation nodes and 1 server node. Simulations of dose have been completed in relation to a range of computational anthropomorphic phantoms, as discussed below, and to the measurement of CTDI (with a 100-mm pencil chamber) both at standard locations in the standard head and body CT dosimetry phantoms and also free-in-air on the axis of rotation.…”
Section: Methodsmentioning
confidence: 99%
“…For the reporting of effective dose, we averaged the male and female effective dose for comparison with the ImPACT hermaphrodite result. As a previous study had shown tube voltage affected the ratio of the organ and effective doses calculated by mathematical phantom software compared to the voxelised phantom software,[23] we restricted the analysis to cases with the most commonly used tube voltage cases in each protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Exceptions to the segmentation in the voxelized phantoms were the skeleton doses, since the endosteal cells and the red bone marrow are small compared to the voxel sizes and therefore voxels of these materials cannot be segmented. For the ICRP 110 phantoms (ICRP 2009) the dose to the skeleton and the dose to the red bone marrow were estimated in a similar way to Jansen and Shrimpton (2011). The endosteal cell dose (skeleton dose) was estimated by correcting individual skeleton doses with the ratio between the mass of the endosteal cells and mass of that individual skeleton.…”
Section: Patient Tablementioning
confidence: 99%